Pre-choice expectations of intangibles - Higher Education (HE) institutions - Shanka, Tekle; Prendergast-Jones, Elizabeth (School of Marketing, Curtin Business School, 2009)
The purpose of this study was to discover the extent to which value-added intangibles influence decision-making of potential university students in the decision-making phase of institution selection. A survey of 500 commerce students in a large university indicated that they expect the institution to offer intangible, value-added services such as skills essential to entering the workforce, management skills and practices, assistance in English and value-added courses such as leadership, teamwork etc in addition to the established academic program. Results revealed that undergraduate students expect short-listed institutions to provide value-added intangibles that develop them professionally and personally in order to increase their employability in the workplace.